2015
DOI: 10.1097/mao.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cochlear Nerve Deficiency Determined Using 3-Dimensional Magnetic Resonance Imaging on Hearing Outcome in Children with Cochlear Implants

Abstract: Although the audiologic and radiologic results may be incompatible, the majority of patients with CND may be well delineated preoperatively using MRI. The type of CND (aplasia/hypoplasia) may affect CI outcomes. Patients implanted on the side with CN hypoplasia are more likely to exhibit favorable results compared with patients implanted on the side with CN aplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…In addition, several studies have reported the possibility of speech development in some implanted children with bilateral CN aplasia that was diagnosed based on MRI results (e.g. Teagle et al, 2010; Wu et al, 2014). Theoretically, these children should have sufficient functional CN fibers in order to achieve speech development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have reported the possibility of speech development in some implanted children with bilateral CN aplasia that was diagnosed based on MRI results (e.g. Teagle et al, 2010; Wu et al, 2014). Theoretically, these children should have sufficient functional CN fibers in order to achieve speech development.…”
Section: Discussionmentioning
confidence: 99%
“…Adunka et al, 2006; Buchman et al, 2011; Sennaroǧlu, 2010; Song et al, 2011; Yamasaki et al, 2015). It is estimated to be present in 1 – 5.3% of children with newly identified hearing loss (Adunka et al, 2006; Buchman et al, 2006; Nakano et al, 2013; Wu et al, 2014), and can occur in up to 50% of children with unilateral severe to profound hearing loss (Clemmens, et al, 2013; Nakano et al, 2013; Roche et al, 2010; Wu et al, 2014). The etiology of CND remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed a significantly positive correlation between the width of BCNC and CN/FN ratio and a significantly negative correlation between the CN/FN ratio and the T level. A recent report suggested a poorer hearing outcome after CI 21 and different responses of CI-elicited cortical auditory evoked potentials in patients with cochlear nerve hypoplasia/aplasia. 22 These results might support different electrical properties of the CN in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, some nerve fibers were available to transmit auditory signals to the brainstem [Casselman et al, 1997;Ozdoğmuş et al, 2004;Warren et al, 2010]. These encouraging results have led to inclusion of ABR testing to augment the imaging data [Kim et al, 2006;Oker et al, 2009;Buchman et al, 2011;Kutz et al, 2011;Pagarkar et al, 2011;Roland et al, 2012;Zhang et al, 2012;Vincenti et al, 2014;Wu et al, 2014]. At times, ABR testing may indicate the presence of a viable nerve in response to electrical stimulation; however, the absence of a response inconsistently predicts the aided auditory benefit [Nikolopoulos et al, 2000;Kim et al, 2008;Roland et al, 2012].…”
Section: Current Imaging Data Does Not Predict Auditorymentioning
confidence: 99%
“…Some children, thought to have absent CVN, nonetheless seemed to benefit from a CI and/or exhibit measurable unaided hearing thresholds [Casselman et al, 1997;Ito et al, 1999;Acker et al, 2001;Govaerts et al, 2003;Zanetti et al, 2006;Bradley et al, 2008;Kang et al, 2010;Warren et al, 2010;Buchman et al, 2011;Kutz et al, 2011;Pagarkar et al, 2011;Zhang et al, 2012;Vincenti et al, 2014;Wu et al, 2014]. The Birman classifications have the benefit of directly cataloging what is seen on imaging and providing an association with outcome, lending it diagnostic usefulness.…”
Section: Introductionmentioning
confidence: 99%